PENGARUH EWOM TERHADAP PURCHASE INTENTION YANG DIMEDIASI OLEH BRAND IMAGE PRODUK SUNSCREEN NIVEA DI KOTA BANDUNG - Husna Amalia; Edi Nurtjahjadi (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
Currently, skincare has almost become a primary need for women. Data sourced from Populix states that as many as 45% of people buy skincare repeatedly at least once a month. With the high frequency of purchasing skincare, it cannot be denied that the growth of the skincare industry in Indonesia is also developing and increasing, but this is not aligned with the decline in the Nivea sunscreen index which experienced a total decline of 8.6% from 2021-2023 in the Top Brand Index. This indicates a decrease in buying interest in Nivea sunscreen. The aim of this study is to examine the influence of electronic word of mouth on purchase intention with the intervening variable being the brand image of Nivea sunscreen products in the city of Bandung. This study uses a quantitative approach, and uses primary data obtained from a questionnaire in the form of a Google form link which is distributed online and then filled in by potential consumers of Nivea sunscreen in Bandung City. Researchers used a Likert scale. Then, the time of data collection in this study was classified as cross-sectional. The sample size was 120 respondents determined using convenience sampling techniques. The results of this research state that EWOM and brand image have a positive and significant influence on purchase intention, EWOM also has a positive and significant influence on brand image. But brand image fails to mediate the influence of EWOM on purchase intention.